Stability Indicating RP-HPLC Method for Quantification of Lefamulin and Its Impurities in Lefamulin Injection: Pharmaceutical sciences- Analytical chemistry - Prabhakara Rao, P. Venkata; Bharath, P.; Mastan Ali, Syed; Ramachandran, D. (International Journal of Life Science and Pharma Research, 2023)
The main aim and objective of the research work is to develop an effective, sensitive, economical, and simple reversephase HPLC method for quantification of Lefamulin and its impurities in the Lefamulin parenteral dosage form. The separation wasachieved using a stationary phase waters X-Bridge shield RP18 (250 x 4.6 mm, 5µ). The mobile phase consists of ammoniumacetate buffer and acetonitrile in the proportion of gradient elution. The flow rate was 1.0 mL/min. Lefamulin was detected usinga UV detector at the wavelength of 210 nm. The column temperature was 25°C, the sample cooler temperature was 5°C, theinjection volume was 10µL, and the run time was 35 minutes. The developed method was validated for parameters per ICHguidelines like accuracy, precision, linearity, specificity, and solution stability. The developed HPLC method was validated withrespect to specificity, the chromatograms were recorded for blank, placebo, standard, and sample solutions of Lefamulin. Specificitystudies reveal that the peaks are well separated from each other. Results were found to be within the acceptance limits for systemprecision and method precision. The linearity results for Lefamulin in the specified concentration range (50.0240-150.0720 µg/mL)are satisfactory, with a correlation coefficient of 0.9999.